Reconstruction of LDPC code sparse check matrix based on modified LBP decoding - ZHANG Tianqi; LI Chunyun; WU Xianyue; WU Yunge (Tongxin xuebao)
In order to reconstruct the sparse check matrix of LDPC code, a sparse check matrix reconstruction algorithm for LDPC code at high BER was proposed based on modified LBP decoding. Firstly, some bits were selected randomly from the codeword matrix to construct the codeword analysis matrix, and Gaussian elimination on it was performed to find the dual space. Secondly, by determining whether the pairwise space vectors were sparse or not, it improved the efficiency of the subsequent suspected check vectors determination. Finally, in the case of insufficient received codes, the known check vectors were combined with the modified LBP decoding method to correct the wrong codes, so as to speed up the reconstruction of the sparse check matrix of LDPC code and improve the reconstruction performance. The simulation results show that the reconstruction rate of sparse check matrix of (648,324) LDPC codes in IEEE 802.11n protocol is improved by 52.16% compared with the existing algorithms, and can reach 92.28% at high BER of 0.004 5.